Impact of vaccination on ICU admissions of hospitalized COVID-19 patients in a country with a heterologous vaccine policy - Yıldırım, Süleyman; Kirakli, Cenk; Özdemir, Yeliz; Tosun, Selma; Ermin, Sinem; Polat, Gülru; Yılmaz, Celalettin; Bilaçeroğlu, Semra; Salık, Bilge; Kömürcüoğlu, Berna; Ödemiş, İlker; Köse, Şükran; et al. (The Journal of Infection in Developing Countries, 2024)
Introduction: Vaccination against coronavirus disease-19 (COVID-19) is highly effective in preventing severe disease and mortality. Adenoviral vector and mRNA vaccines were effective against intensive care unit (ICU) admission, but the effectiveness of inactivated vaccine on ICU admission was unclear. We aimed to evaluate the effect of vaccination status on ICU admission in hospitalized COVID-19 patients in a country with heterologous vaccination policy. Methodology: This is a retrospective multicenter study conducted in three hospitals in Izmir, Turkey between 1 January 2021 and 31 March 2022. Patients aged ≥ 18 years and hospitalized due to COVID-19 were included in the study. Patients who had never been vaccinated and patients who had been vaccinated with a single dose were considered unvaccinated. A logistic regression analysis was performed for evaluating risk factors for ICU admission. Results: A total of 2,110 patients were included in the final analysis. The median age was 66 years (IQR, 53-76 years) and 54% of the patients were vaccinated. During the study period, 407 patients (19.3%) were transferred to the ICU due to disease severity. Patients who were admitted to the ICU were older (median age 68 vs. 65 years, p < 0.001); and the number of unvaccinated individuals was higher among ICU patients (57% vs. 45%, p < 0.001). In multivariate regression analysis, being unvaccinated was found to be the most important independent risk factor for ICU admission with an OR of 2.06 (95% CI, 1.64-2.59). Conclusions: Vaccination against COVID-19 is effective against ICU admission and hospital mortality.